2018
DOI: 10.1136/archdischild-2017-313309
|View full text |Cite
|
Sign up to set email alerts
|

More medicines for children: impact of the EU paediatric regulation

Abstract: The entry into force of the Paediatric Regulation has had a positive impact on paediatric drug development with more medicines available for children in the EU and substantially more information available for clinicians on paediatric use in the product information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 4 publications
3
24
0
1
Order By: Relevance
“…Table 1 summarises the main differences in definition, regulatory approach and (post)marketing. Particularly for children, this differs significantly from paediatric medicine development 8–11…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarises the main differences in definition, regulatory approach and (post)marketing. Particularly for children, this differs significantly from paediatric medicine development 8–11…”
Section: Introductionmentioning
confidence: 99%
“…Lack of clinical studies are not the only reason for a medicine being off‐label. It is a quite common situation that pharmaceutical companies research on medicines for children are not completed, or fail to put the product on the market, maybe due to lack of profit, leaving paediatricians to have no other choice but use these in off‐label manner . The current use of unlicensed and insufficiently studied medicines in neonates, children and adolescents, increases the risk of facing unexpected adverse drug reactions related to administration and dosage, but also for the administration of too low exposures with insufficient efficacy .…”
Section: Nordic Network For Drug Development In Childrenmentioning
confidence: 99%
“…Informed consent Parents and/or legal guardians of children and adult patients participating in these clinical trials gave their informed consent prior to their inclusion in the studies reported in this manuscript. Hospital Clínico Universitario, Valencia, Spain 10 Hospital Universitario Marqués de Valdecilla, Santander, Spain 11 Hospital Universitario Torrecárdenas, Almeria, Spain 12 Hospital Universitario Miguel Servet, Saragossa, Spain 13 Hospital Universitario Nuestra Señora de la Candelaria, Santa Cruz de Tenerife, Spain 14 Hospital Alvaro Cunqueiro, Vigo, Spain 15 Hospital Universitario Carlos Haya, Malaga, Spain 16 Hospital Universitario Virgen de la Macarena, Seville, Spain…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%